Computational Prediction of Ferro‐ and Piezoelectricity in Lead‐Free Oxyhydrides Ln2H4O (Ln = Y, La). Issue 12 (27th September 2019) - Pishtshev, Aleksandr; Strugovshchikov, Evgenii
Abstract: One of the most significant aspects of crystal chemistry of multianionic oxyhydrides is the possibility of flexible regulation of the composition–structure–function relationships. In the context of competitive configurations of different anions in the crystal lattice, this may afford formation of a number of stable stoichiometric phases without inversion symmetry. In the present work, it is shown that semiconducting layered oxyhydrides with the composition Ln2 H4 O (Ln = Y, La) have an attractive potential for the design of novel lead‐free ferro‐ and piezoelectric systems. By means of density functional theory‐based computational simulations it is predicted that polar monoclinic and orthorhombic phases of the bulk Ln2 H4 O may exhibit exceptional ferro‐ and piezoelectric properties as well as electromechanical coupling characteristics that are especially suitable for the piezoelectric devices working in a shear mode. It is shown that quantitative estimates of ferro‐ and piezoelectric characteristics are well matching with the specification data of advanced ferroelectric solid solutions. Thus, our prediction of lead‐free piezoelectric systems forms a solid and technologically reliable basis for the development of effective and nonhazardous materials. Abstract : Monoclinic, orthorhombic, and trigonal polar phases of the semiconducting layered oxyhydrides Ln2 H4 O (Ln = Y, La) have an attractive potential for the design of novel lead‐free ferro‐ and piezoelectric systems. The acentric packing of anionic groups provides layered lattice orderings without inversion symmetry. Control of polarity can be governed via the change of anionic configurations.